The SITMAR liners : past and present - Plowman, Peter (Rosenberg, 2004)
This story of the Sitmar Liners is written primarily from an Australian perspective, but it also covers the general development of the company and its operations throughout the world.Sitmar was sold to the P & O Group in July 1988 and the sale was totally unexpected, but the Sitmar name did survive for a few more years in Australia, where the new operation was known as P & O Sitmar Cruises until 1991, when it was renamed P & O Holidays. The link between Australia and the former Sitmar Cruises liners continues to this day.